Analysis of Engine Maintenance Techniques in Double-Cabin Vehicle Units Using Modularity Design Method at PT Wahyu Putra Mandiri Perkasa - Tsabita Chaerunisa Tandriajeng; Wiwik Handayani (PT. Publikasiku Academic Solution, 2023)
Companies that providing motorised vehicle rental services specialising in coal mining areas have to go the extra mile in carrying out maintenance due to unexpected damage by the maintenance schedule. This research aims to discover problems related to constraints on the maintenance system carried out so that it is less efficient and effective in its implementation. Preventive maintenance with a modularity design method collects data with documentation, interviews, and observations. The analysis technique determines the company’s total cost (Initial TC). It continues determining the total cost of the proposal (Proposed TC) which is processed using app. Minitab 2021. The results of this study indicate that maintenance costs using preventive maintenance with the modularity design method are lower and more efficient than maintenance costs using corrective maintenance carried out by the company.